2022
DOI: 10.1177/26350106221110817
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Distress in Emerging Adulthood: Content Validity of the Problem Areas in Diabetes—Emerging Adult Version (PAID-EA) Using Qualitative Analysis

Abstract: Purpose: The purpose of this study was to explore the emotional work of diabetes during emerging adulthood and to explicate the validity of a newly developed measure of diabetes distress (DD) for use with emerging adults living with type 1 diabetes mellitus (T1DM), the Problem Areas in Diabetes—Emerging Adult version (PAID-EA). Methods: Young people ages 18 to 30 with T1DM were recruited online to complete a cross-sectional survey including measures of DD, depressive symptomology, and the PAID-EA. To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…MAXQDA (V.22.1.1) was used to conduct thematic analysis across transcripts as follows: a qualitative codebook with a priori deductive codes was developed using the interview guide and preliminary themes based on literature review,14–29 and inductive codes were developed during transcript review and analyst discussion. Each transcript was independently coded in its original language by three coders who were fluent in the language in which the interview was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…MAXQDA (V.22.1.1) was used to conduct thematic analysis across transcripts as follows: a qualitative codebook with a priori deductive codes was developed using the interview guide and preliminary themes based on literature review,14–29 and inductive codes were developed during transcript review and analyst discussion. Each transcript was independently coded in its original language by three coders who were fluent in the language in which the interview was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…4 10 To equitably address the complex and evolving needs of diabetes care in the pandemic and post-pandemic eras, research must adequately capture the context of care among patients and health systems in communities that are disparately affected by these challenges and yet often underrepresented in research. 13 Prior research has found that social determinants of health, such as financial factors, access to healthcare and psychosocial support have substantial impacts on patients' experience with and outcomes of diabetes care [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and that these experiences can differ across other, intersecting factors, 19 such as race, ethnicity, language and rurality. However, few of these prior studies were conducted during or after the pandemic's onset, with most recent studies examining the experiences of patients living outside the USA during that time.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations